Criando valor por meio da servitização digital: um estudo exploratório em uma firma de equipamentos metal mecânico - Kunz, Ildo José (Universidade do Vale do Rio dos Sinos, 2025)
This study aimed to analyze how digital servitization (DS) can add value to customers and, consequently, increase revenue from product-service systems in a large familyowned company in the metalworking sector. The research, focusing on the case of SAUR company, addresses the "servitization paradox", which describes the challenges companies face in achieving financial returns when transitioning to servicebased models. Using a qualitative and exploratory single-case study approach and the theoretical lens of Knowledge-Based Dynamic Capabilities (KBDC), the company's transformation journey and its ecosystem were investigated. The findings revealed that a successful transition to DS depends on a synergistic orchestration of internal capabilities, external ecosystem management, and the application of enabling technologies. Among the main barriers identified are cultural resistance (both internal and external), a shortage of skilled professionals, and deficiencies in connectivity infrastructure. In response, SAUR demonstrated the practical application of KBDCs: (i) Sensing, by actively monitoring customer needs through tools like Customer Relationship Management (CRM); (ii) Seizing, by capturing opportunities with technologies such as IoT and telemetry to create new business models (e.g., pay-peruse); and (iii) Transformation, by reconfiguring its structure with interdisciplinary teams and innovation units, such as SAUR Tech. This strategy resulted in a 220% growth in service revenue between 2015 and 2024, demonstrating that the paradox was overcome. The conclusions reinforce that DS is a complex and non-linear process. The study contributes to theory by providing a practical and empirically validated model of the DS journey. For managerial practice, it offers a roadmap for transformation, highlighting realistic challenges and effective strategic responses. Limitations, such as the focus on a single case, open avenues for future research, including quantitative studies to validate the model, longitudinal studies to track the evolution of DS, and investigations into emerging technologies and human factors in organizations.
Keywords: Servitização digital; Criação de valor; Capacidades dinâmicas; Modelo de negócio; Indústria 4.0; Grande empresa familiar; Digital servitization; Value creation; Dynamic capabilities; Business model; Industry 4.0; Large family-owned enterprise; ACCNPQ::Engenharias::Engenharia de Produção